2011
DOI: 10.1111/j.1755-5949.2011.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Zinc in a Rat Model of Epilepsy

Abstract: The present study highlights the antiepileptic role that could be played by Zn, when given in appropriate doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…This controversy may be a result of differences in zinc rout administration and difference in sensitivity of these patients in response to zinc components. Since Zn is a voltage sensitive calcium channels blocker and has antiepileptic role in appropriate doses [25,26], it may be blocked prolactin inhibitor factor secretion in hypothalamus and caused increased prolactin secretion in adenohypophsis [27,28]. Moreover, present results showed that serum LH level was decreased in experimental group but did not show any changes in serum FSH level.…”
Section: Discussionsupporting
confidence: 53%
“…This controversy may be a result of differences in zinc rout administration and difference in sensitivity of these patients in response to zinc components. Since Zn is a voltage sensitive calcium channels blocker and has antiepileptic role in appropriate doses [25,26], it may be blocked prolactin inhibitor factor secretion in hypothalamus and caused increased prolactin secretion in adenohypophsis [27,28]. Moreover, present results showed that serum LH level was decreased in experimental group but did not show any changes in serum FSH level.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, it has been proposed that zinc could have a neurotoxic role where excessive zinc could impair the protein degradation pathway and might be a crucial factor mediating neuronal death [202]. In line with this, another study demonstrated that the pretreatment with a high dose of zinc exacerbated pilocarpine-induced seizures, whereas a medium dose of zinc reduced the severity of limbic seizures [203]. In appropriate doses, zinc plays an important role in mitigating seizures by suppressing oxidative stress, apoptotic activity and IL-1β levels, resulting in neuroprotective effects [203].…”
Section: Zinc Seizures and Epilepsymentioning
confidence: 83%
“…The PTZ test identifies drugs with efficacy against generalized nonconvulsive seizures . The pilocarpine‐treated rat model is also adopted in many studies , and the changes along with NMDAR upregulation in parahippocampal areas such as the EC have been reported in this model . In the low‐Mg 2+ /high‐K + ‐induced epilepsy model, the generation of SLEs has been attributed to the reduced surface charge of neuronal membrane and the disinhibition of NMDAR followed by calcium influx .…”
Section: Discussionmentioning
confidence: 99%